2001
DOI: 10.1186/ar144
|View full text |Cite
|
Sign up to set email alerts
|

The stressed synovium

Abstract: ERK = extracellular signal-regulated protein kinase; HSF-1 = heat shock factor-1; HSP = heat shock protein; IL = interleukin; JNK = c-Jun aminoterminal kinase; MAPK = mitogen-activated protein kinase; NF-κB = nuclear factor-κB; RA = rheumatoid arthritis; SAPK = stress-activated protein kinase; TNF = tumour necrosis factor. Available online http://arthritis-research.com/content/3/2/080 IntroductionPatients with rheumatoid arthritis (RA) are confronted with a multitude of stressful events during the course of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Likewise, increased expression of human HSP60 in the synovium of patients with rheumatoid arthritis has been demonstrated [24], [46]. A similar upregulation is likely to happen in the synovium of SpA patients, which could be the explanation of the increased levels of antibodies against human HSP60 in SpA patients compared with healthy controls seen in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…Likewise, increased expression of human HSP60 in the synovium of patients with rheumatoid arthritis has been demonstrated [24], [46]. A similar upregulation is likely to happen in the synovium of SpA patients, which could be the explanation of the increased levels of antibodies against human HSP60 in SpA patients compared with healthy controls seen in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…It was recently demonstrated that these endogenous ligands (natural adjuvants) can activate dendritic cells in conditions of cell stress and/or structural cell damage, leading to primary immune responses and initiation of autoimmunity (13, 39, 40). Consistent with this scenario, several pathways of stress‐signaling molecules are found to be activated in the synovial membrane and fluid of RA patients (41). It is conceivable that these local endogenous ligands activate TLR‐2– and TLR‐4–bearing dendritic cells, macrophages, and fibroblasts, which leads to an increased secretion of proinflammatory cytokines such as IL‐12, IL‐18, IL‐1, and TNFα.…”
Section: Discussionmentioning
confidence: 71%
“…These pathways are found to be activated in the synovial tissue of RA patients and induced by pro-inflammatory cytokines [49]. In particular, the p38␣ has been localized in synovial macrophages, but not in RA-SF, which preferentially express the ␤ (in the lining and sublining) and ␦ isoforms (at sites of joint destruction).…”
Section: Cytokine-dependent Pathwaysmentioning
confidence: 98%